2019
DOI: 10.14260/jemds/2019/792
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training on Energy Conservation Strategies, Fatigue, and Self-Caring among Women with Breast Cancer Undergoing Chemotherapy in Zahedan Medical Sciences Hospitals in 2018-2019

Abstract: BACKGROUNDFatigue is one of the most common cancer-related problems. Fatigue-reduction nondrug methods include energy conservation strategies and improving self-caring efficacy. The aim of the present study was to determine the effect of energy conservation strategies training on fatigue and caring self-efficacy in cancer patients. METHODSIt was a single-blind clinical trial study performed on 80 breast cancer patients in educational hospitals in Zahedan (Iran) selected by simple random sampling. After randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Khozimeh et al showed that the use of energy-saving strategies significantly reduced the patient's fatigue compared to the control group and the patients in the intervention group better managed their fatigue. Their main energy-saving strategy was to create a balance between the rest and activity times during fatigue induced by the disease (45). Another study by Abdollahi and Shujaedin suggested that the training protocol improved all aspects of the quality of life and increased physical performance in the intervention group compared to the control group (46), as was evident in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Khozimeh et al showed that the use of energy-saving strategies significantly reduced the patient's fatigue compared to the control group and the patients in the intervention group better managed their fatigue. Their main energy-saving strategy was to create a balance between the rest and activity times during fatigue induced by the disease (45). Another study by Abdollahi and Shujaedin suggested that the training protocol improved all aspects of the quality of life and increased physical performance in the intervention group compared to the control group (46), as was evident in the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Educational interventions are believed to improve cancer-related fatigue30 and there is some evidence to support this in earlier stages of CKD 31. Likewise, education about energy conservation is another approach to manage fatigue that has shown a significant reduction in fatigue in other chronic diseases, including multiple sclerosis32 and cancer 33 34. However, its effectiveness is yet to be tested in the HD population.…”
Section: Introductionmentioning
confidence: 99%